Chemo-specific designs for the enumeration of circulating tumor cells: advances in liquid biopsy. Issue 13 (22nd January 2021) - Singh, Balram; Arora, Smriti; D'Souza, Alain; Kale, Narendra; Aland, Gourishankar; Bharde, Atul; Quadir, Mohiuddin; Calderón, Marcelo; Chaturvedi, Pankaj; Khandare, Jayant
Abstract : Chemical platforms for isolation and enumeration of Circulating Tumor Cells (CTCs) in advancing the relevance of liquid biopsy in cancer diagnostics and treatment. Abstract : Advanced materials and chemo-specific designs at the nano/micrometer-scale have ensured revolutionary progress in next-generation clinically relevant technologies. For example, isolating a rare population of cells, like circulating tumor cells (CTCs) from the blood amongst billions of other blood cells, is one of the most complex scientific challenges in cancer diagnostics. The chemical tunability for achieving this degree of exceptional specificity for extra-cellular biomarker interactions demands the utility of advanced entities and multistep reactions both in solution and in the insoluble state. Thus, this review delineates the chemo-specific substrates, chemical methods, and structure–activity relationships (SARs) of chemical platforms used for isolation and enumeration of CTCs in advancing the relevance of liquid biopsy in cancer diagnostics and disease management. We highlight the synthesis of cell-specific, tumor biomarker-based, chemo-specific substrates utilizing functionalized linkers through chemistry-based conjugation strategies. The capacity of these nano/micro substrates to enhance the cell interaction specificity and efficiency with the targeted tumor cells is detailed. Furthermore, this review accounts for the importance of CTC capture and other downstream processes involving genotypic and phenotypic CTC analysis in real-time for the detection of the early onset of metastases progression and chemotherapy treatment response, and for monitoring progression free-survival (PFS), disease-free survival (DFS), and eventually overall survival (OS) in cancer patients.